"New Normal" Home Chemotherapy in Thailand: How the Challenging Roles of Nurses Are Changing? - Werayuth Srithumsuk; Kouchchukorn Wangnum (Elsevier, 2021)
Home chemotherapy is a service administered by oncology and home healthcare (HHC) nurses which provides a package of care to support the administration of chemotherapy to patients in their homes. The coronavirus disease 2019 (COVID-19) pandemic and new normal situation have shifted home chemotherapy administration from hospitals and become indispensable for patient care. Many cancer centers and hospitals in Thailand ad hoc home chemotherapy during the COVID-19 and new normal situation to maintain the effectiveness of chemotherapy for cancer patients at home; preventing COVID-19 disease infection is the most important concern. The purpose of this article is to describe the lessons learned for delivering home chemotherapy to cancer patients from oncology nurses during the COVID-19 pandemic and the new normal situation in Thailand. Nurses are at the forefront of the current pandemic and are taking a proactive approach with multidisciplinary teams to participate in the pandemic planning within their health organizations. The role of nurses in home chemotherapy in the new normal must be stricter than usual. Both oncology and HHC nurses play a different role for home chemotherapy, but cooperation is important to improve the quality of life and maintain the quality of care with effective treatment. Therefore, the lessons learned regarding home chemotherapy during the new normal in Thailand is a good example for other countries to develop appropriate care for cancer patients in the pandemic situation from the perspective of nurses' role.